Bias of s 2 in the Linear Regression Model With Correlated Errors - Kiviet, Jan F.; Kramer, Walter (The Review of Economics and Statistics, 1992)
The authors consider the relative bias of the OLS-based estimate s(squared) of the disturbance variance in the linear regression model when disturbances are stationary AR(1). They improve upon previous bounds for the bias and show that E(s[squared]/[sigma squared]) tends to zero as autocorrelation increases whenever there is an intercept in the regression. Copyright 1992 by MIT Press.